Vestibular dysfunction and its association with cognitive impairment and dementia - Aedo-Sanchez, Cristian; Riquelme-Contreras, Patricio; Henríquez, Fernando; Aguilar-Vidal, Enzo (Frontiers in Neuroscience, 2024)
The vestibular system plays an important role in maintaining balance and posture. It also contributes to vertical perception, body awareness and spatial navigation. In addition to its sensory function, the vestibular system has direct connections to key areas responsible for higher cognitive functions, such as the prefrontal cortex, insula and hippocampus. Several studies have reported that vestibular dysfunction, in particular bilateral vestibulopathy, is associated with an increased risk of cognitive impairment and the development of dementias such as Alzheimer’s disease. However, it is still controversial whether there is a causal relationship between vestibular damage and cognitive dysfunction. In this mini-review, we will explore the relationship between the vestibular system, cognitive dysfunction and dementia, hypotheses about the hypothesis and causes that may explain this phenomenon and also some potential confounders that may also lead to cognitive impairment. We will also review multimodal neuroimaging approaches that have investigated structural and functional effects on the cortico-vestibular network and finally, describe some approaches to the management of patients with vestibular damage who have shown some cognitive impairment.